Consumer Perception and Attitude Towards Foreign Verus Domestic Apparel in Thailand - Sae-jiu, Sirirat (2007)
The purpose of this dissertation was to study whether or not consumer perceptions and attitudes toward purchasing domestic versus imported apparel product differ among young consumers in Thailand. Variables to be investigated include apparel attributes and demographic characteristics. Also, the effects of country of origin and consumer ethnocentrism were examined.